Boosting Elementary Students’ Learning Interest: The Impact of The Question-And-Answer Method - Irianto, Tenri Ugi; Timang, Nelsy Jenifer (Applied Linguistics: Innovative Approaches and Emerging Trends, 2024)
This study examines the impact of the question-and-answer teaching method on elementary students’ interest in learning Indonesian at State Elementary School Inpres Dok VIII Atas Jayapura, Indonesia. Utilizing a qualitative approach, the research investigates students’ joy in learning, active participation, and the effectiveness of teacher strategies in fostering engagement. Findings indicate that the question-and-answer method enhances student creativity, improves learning outcomes, and develops critical thinking. However, challenges such as language anxiety and focus issues persist. The study emphasizes the importance of creative and dynamic teaching methods to boost student motivation and participation, proposing strategies for reducing classroom disengagement and enhancing interaction.